Reputation As Mediation To The Influence Of Brand Equity On Revisit Intention - Sunarta Sunarta; Eti Rochaeti; Budi Permana Yusuf (Agregat: Jurnal Ekonomi dan Bisnis, 2020)
The purpose of this study was to analyze the influence of brand equity on revisit intention mediated by reputation. This research is a descriptive study with a quantitative approach. The data source used is primary data. Primary data are the results of interviews with outpatient at Islamic hospitals in Jakarta and processed using regression analysis. The results of this study show that the hospital's excellent reputation is highly significant for the value of hospital brand image and its patients revisit intention in the near future. This study was conducted using a series of surveys supported with instruments that have been tested and approved to collect accurate data about brand equity and hospital's reputation as related to the patient's revisit intention in the Islamic Hospitals in D.K.I. Jakarta. It is expected that this study could give a contribution to the improvement of medical policy in general and especially on the development of medical tourism in D.K.I. Jakarta.